Respuesta :
Answer:
1.
[tex]t = \sqrt(2h/g)[/tex]
2.
[tex]ax = F/m[/tex]
3.
[tex]x=\frac{Fh}{mg}[/tex]
4.
[tex]a=\sqrt(F^2/m^ + g^2)[/tex]
5.
(a)
[tex]t = \sqrt\frac{2h}{g+{Fsin\theta}{m}}[/tex]
(b)
[tex]ax= \frac{Fcos\theta}{m}[/tex]
(c)
[tex]x=\frac{hFcos\theta}{m(g+\frac{Fsin\theta}{m}}[/tex]
(d)
[tex]a=\sqrt((\frac{F^2cos^2\theta}{m^2}+(g+\frac{Fsin\theta}{m})^2)[/tex]
Explanation:
1.
[tex]h = 0.5gt^2[/tex]
Therefore, [tex]t = \sqrt(2h/g)[/tex]
2.
[tex]ax = \frac{F}{m}[/tex]
(3)
[tex]x = 0.5axt^2 = \frac{0.5F/m}{2h/g} = \frac{Fh}{mg}[/tex]
(4)
[tex]a = \sqrt(ax^2 + g^2) = \sqrt(F^2/m^ + g^2)[/tex]
5
(a)
[tex]h=0.5(g+\frac{Fsin\theta}{m}[/tex]
[tex]t = \sqrt\frac{2h}{g+{Fsin\theta}{m}}[/tex]
(b)
[tex]ax= \frac{Fcos\theta}{m}[/tex]
(c)
[tex]x=0.5axt^2[/tex]
[tex]x= 0.5\frac{Fcos\theta}{m}t^2[/tex]
[tex]x=\frac{hFcos\theta}{m(g+\frac{Fsin\theta}{m}}[/tex]
(d)
[tex]a=sqrt(ax^2+ay^2)=\sqrt((\frac{F^2cos^2\theta}{m^2}+(g+\frac{Fsin\theta}{m})^2)[/tex]
Acceleration is the rate of change of velocity with respect to time. Stone's acceleration is [tex]a = \sqrt{(\dfrac{F}{m})^2 + g^2}\\\\[/tex].
What is acceleration?
Acceleration is the rate of change of velocity with respect to time.
A.) We know that according to the second equation of motion for the vertical moment we can write the equation as,
[tex]S = ut + \dfrac{1}{2}gt^2[/tex]
Now, since the initial velocity of the stone is 0, and the S the distance that will be covered by the stone is the height of the cliff h. therefore,
[tex]h = \dfrac{1}{2}gt^2\\\\t= \sqrt{\dfrac{2h}{g}}[/tex]
B.) we know that the force is the product of mass and acceleration, therefore, the acceleration of the stone can be written as,
[tex]F = m \times a_x\\\\a_x = \dfrac{F}{m}[/tex]
C.) We know that according to the second equation of motion for the horizontal moment we can write the equation as,
[tex]S = ut + \dfrac{1}{2}at^2[/tex]
Now, since the initial velocity of the stone is 0,
[tex]x = \dfrac{1}{2}a_xt^2[/tex]
We know the values of [tex]a_x[/tex], also, the value of t, therefore,
[tex]x = \dfrac{1}{2} \times \dfrac{F}{m} \times (\sqrt{\dfrac{2h}{g}})^2\\\\\\x = \dfrac{1}{2} \times \dfrac{F}{m} \times {\dfrac{2h}{g}}\\\\\\x =\dfrac{Fh}{mg}[/tex]
D.) The magnitude of the stone's acceleration while it is falling.
Stone's acceleration while it is falling, is the resultant of the vertical and the horizontal acceleration that is working on the stone,
[tex]a =\sqrt{a_x^2 + a_y^2}\\\\a = \sqrt{(\dfrac{F}{m})^2 + g^2}\\\\[/tex]
E.) If the force is applied from an angle θ, then,
1.
[tex]h = \dfrac{1}{2}(g+ \dfrac{F\ \Sin \theta}{m})\\\\t= \sqrt{\dfrac{2h}{(g+ \dfrac{F\ \Sin \theta}{m}}}[/tex]
2.
[tex]a_x = \dfrac{F\ Cos \theta}{m}[/tex]
3.
[tex]x = 0.5a_xt\\\\x = 0.5 \dfrac{F\ Cos \theta}{m}t^2\\\\x = \dfrac{h\ F\ Cos\theta}{m(g+\dfrac{F\ Sin\theta}{m})}[/tex]
4.
[tex]a=\sqrt{a_x^2+a_y^2}\\\\a = \sqrt{(\dfrac{F\ Cos \theta}{m})^2+(g+ \dfrac{F\ \Sin \theta}{m})^2}[/tex]
Learn more about Acceleration:
https://brainly.com/question/2437624